Nanostructured titanium regulates osseointegration via influencing macrophage polarization in the osteogenic environment - Wang J (Dove Medical Press, 2018)
Jinjin Wang,1,2,* Fanhui Meng,3,* Wen Song,3,* Jingyi Jin,2 Qianli Ma,2 Dongdong Fei,1 Liang Fang,2 Lihua Chen,2 Qintao Wang,1 Yumei Zhang3 1State Key Laboratory of Military Stomatology & National Clinical Research Center for Oral Diseases & Shaanxi Engineering Research Center for Dental Materials and Advanced Manufacture, Department of Periodontology, School of Stomatology, The Fourth Military Medical University, Xi’an, Shannxi Province, China; 2Department of Immunology, School of Basic Medicine, The Fourth Military Medical University, Xi’an, Shannxi Province, China; 3State Key Laboratory of Military Stomatology & National Clinical Research Center for Oral Diseases & Shaanxi Key Laboratory of Stomatology, Department of Prosthodontics, School of Stomatology, The Fourth Military Medical University, Xi’an, Shannxi Province, China *These authors contributed equally to this work Introduction: Fabricating nanostructured surface topography represents the mainstream approach to induce osteogenesis for the next-generation bone implant. In the past, the bone implant was designed to minimize host repulsive reactions in order to acquire biocompatibility. However, increasing reports indicate that the absence of an appropriate immune response cannot acquire adequate osseointegration after implantation in vivo. Materials and methods: We prepared different topographies on the surface of titanium (Ti) specimens by grinding, etching and anodizing, and they were marked as polished specimen (P), specimen with nanotubes (NTs) in small diameters (NT-30) and specimen with NTs in large diameters (NT-100). We evaluated the ability of different topographies of the specimen to induce osteogenic differentiation of mice bone marrow mesenchymal stem cells (BMSCs) in vitro and to induce osseointegration in vivo. Furthermore, we investigated the effect of different topographies on the polarization and secretion of macrophages, and the effect of macrophage polarization on topography-induced osteogenic differentiation of mice BMSCs. Finally, we verified the effect of macrophage polarization on topography-induced osseointegration in vivo by using Cre*RBP-Jfl/fl mice in which classically activated macrophage was restrained. Results: The osteogenic differentiation of mice BMSCs induced by specimen with different topographies was NT-100>NT-30>P, while the osseointegration induced by specimen with different topographies in vivo was NT-30>NT-100>P. In addition, specimen of NT-30 could induce more macrophages to M2 polarization, while specimen of P and NT-100 could induce more macrophages to M1 polarization. When co-culture mice BMSCs and macrophages on specimen with different topographies , the osteogenic differentiation of mice BMSCs was NT-30>NT-100≥P. The osseointegration induced by NT-100 in Cre*RBP-Jfl/fl mice was much better than that of wild type mice. Conclusion: It is suggested that the intrinsic immunomodulatory effects of nanomaterials are not only crucial to evaluate the in vivo biocompatibility but also required to determine the final osseointegration. To clarify the immune response and osseointegration may be beneficial for the designation and optimization of the bone implant. Keywords: nanomaterials, topography, immunomodulatory effects, macrophage polarization, osseointegration